Independent mobility in relation to weekday and weekend physical activity in children aged 10-11 years: The PEACH Project - Davis Laura; Griew Pippa; Cooper Ashley R; Page Angie S; Hillsdon Melvyn (BMC, 2009)
Abstract Background Children's independent mobility has fallen in recent years and may in part explain reported declines in physical activity in young people. This cross-sectional study investigated whether independent mobility in boys and girls was related to objectively measured physical activity. Methods Thirteen hundred and seven 10-11 year old boys and girls from 23 schools in a large UK city took part. Measures included objectively recorded physical activity (accelerometer (Actigraph GT1M)), height (m) and weight (kg), a newly developed scale for local (Local-IM) and area independent mobility (Area-IM), minutes of daylight after school, level of neighbourhood deprivation and pubertal status. Results Boys had greater Local-IM, Area-IM and physical activity (average weekday and weekend counts per minute) compared to girls. In linear regression analyses (adjusting for minutes of daylight after school, neighbourhood deprivation, pubertal status and body mass index) higher scores for Local-IM and Area-IM were significantly (p < 0.01) related to higher levels of physical activity on weekdays for boys and girls. For weekend physical activity, only Local-IM in girls remained significant (p < 0.05) in the model. Conclusion Independent mobility appears to be an important independent correlate of weekday physical activity for both boys and girls.